2016
DOI: 10.3109/21678421.2016.1165258
|View full text |Cite
|
Sign up to set email alerts
|

Single and modeled multifrequency electrical impedance myography parameters and their relationship to force production in the ALS SOD1G93A mouse

Abstract: Objective The relationship between muscle force production in ALS SOD1G93A mice and single and modeled multifrequency electrical impedance myography (EIM) parameters is unknown. We evaluated the relationship between multifrequency EIM data and paw grip and in situ force measurements, as well to standard measures in including body weight and compound motor action potential (CMAP) amplitude. Methods Twenty-nine SOD1 G93A mice aged 13-18 weeks (approximately 4-5 per week) and a group of similarly aged wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…Those studies identified a strong relationship between EIM and these parameters. In addition, we have evaluated the relationship between EIM and force output in ALS mice and again found a robust relationship . It is perhaps not unexpected, therefore, that we identified a similar relationship between EIM and muscle fiber size here.…”
Section: Discussionsupporting
confidence: 71%
“…Those studies identified a strong relationship between EIM and these parameters. In addition, we have evaluated the relationship between EIM and force output in ALS mice and again found a robust relationship . It is perhaps not unexpected, therefore, that we identified a similar relationship between EIM and muscle fiber size here.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies suggest that multi-frequency EIM is a better option in diagnosing normal from diseased muscle and even in distinguishing different neuromuscular diseases [26, 32, 37, 55]. By profiling three impedance parameters (resistance, reactance and phase), we obtained distinctive patterns between normal and affected dogs, suggesting EIM is a sensitive measure in the canine model of DMD (Fig 3).…”
Section: Discussionmentioning
confidence: 73%
“…Since sex may influence EIM [57], we need to expand our study to include both male and female normal dogs; (3) for the convenience, we have only studied one dog muscle (biceps femoris) in the current study. With the further development of the technique (for example, the custom-designed EIM apparatus), we may evaluate a variety of different surface muscles to gain a more global evaluation of the disease in the dog model; (4) in this study, we have focused on correlating the pathological findings with the EIM data, there is a need to determine whether the EIM data relate well with the results of physiological assays such as muscle force measurement, gait analysis and activity monitoring in dogs [12, 17, 18]; results in mdx mice (Seward B. Rutkove, unpublished results) and ALS mice suggest a relationship between muscle force measurement and impedance values [26]. Similarly, it will be worthwhile to compare EIM with muscle ultrasound and MRI [38, 40]; (5) as a cross-sectional study, we only selected two age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Multifrequency resistance and reactance data were reduced to a set of 4 standard modeled parameters (the Cole parameters) by using the standard impedance model described elsewhere. 6,11,12 The first parameter is R 0 , which would be the highest resistance value were it possible to measure at 0 Hz frequency. The second parameter is R inf , which would be lowest resistance value were it possible to measure at infinite frequency.…”
Section: Methodsmentioning
confidence: 99%